(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper is based on the major research project sponsored by UGC completed by the author in the capacity of the principal investigator. Various field surveys were conducted as part of the project to study the importance and relevance of the formal financial sector in meeting the financial needs of the unincorporated sector. The growth of the Indian economy is largely driven by the informal sector. It plays a crucial role in our economy in terms of employment and its contribution to national income, savings, and capital formation. Notwithstanding its importance in the economy, the unfortunate state of affairs is that it remains starved of capital. Since it fails to get access to the organized sources of finance, it is forced to fall upon the unorganized credit market, getting funds often at exorbitant interest rates. The major results presented here help to explore and understand the intricacies in the working of the Indian financial system, with particular reference to financing the requirements of the so-called informal sector. The position of the national capital region in this context has been separately analyzed.